Kinematics and kinetics assessment of lower limb movement in bharatanatyam dancers / Gowri Gopalakrishnan - Gowri , Gopalakrishnan (2019)
Bharatanatyam is one of the eight recognised classical Indian dance genres which is originated from South India. The major difference between Bharatanatyam and other dance form is the wearing of dancing bells at both ankles. Our literature findings support that the bells add stress to the dancer’s feet which overloads the connective tissues of legs and lead to overextension, tendon strain and other connective tissue injuries. The aim of this study is to conduct kinematics and kinetics assessment of lower limb movement in Bharatanatyam dancers. As walking is one of the most common and most important forms of human movement, our study is based on walking gait. Six young adults (three dancers and three non-dancers) recruited to participate on this study. Each subject was instructed to perform five trials of the gait at self-initiated walking speed on six meters of walking platform with bare foot and another five trials with dancing bells attached to both ankles. Results showed that wearing dancing bells seems to impact dancer's ground reaction force by producing high vertical ground reaction peak at maximum loading response (double support phase) and low anterior-posterior force peak at minimum mid-stand phase. Besides that, wearing dancing bells observed to impact our control group kinematics data as we found angular increase/reduction, especially on the frontal plane which involves abduction/adduction especially on ankle and knee. The findings suggest the intense dancing activities and wearing dancing bells have the capacity to change the walking pattern of an individual.